Caspase-mediated degradation of human 5-lipoxygenase in B lymphocytic cells - Werz, Oliver (National Academy of Sciences, 2005)
5-Lipoxygenase (5-LO) is a tightly regulated enzyme in the synthesis of bioactive lipids from arachidonic acid. Here, we demonstrate that 5-LO is regulated by caspases, which are signaling molecules that control critical biological processes by means of specific limited proteolysis. Cell splitting of the Epstein–Barr virus-transformed B lymphocytic cell line BL41-E95-A caused a pronounced, but transient, reduction of functional 5-LO protein, ac-companied by the appearance of a 62-kDa 5-LO cleavage product. In parallel, splitting of BL41-E95-A cells induced activation of caspase-6 (casp-6) and casp-8. Caspase activation and 5-LO degradation were blocked by the protein-synthesis inhibitor cycloheximide, and cell-permeable peptide inhibitors of casp-6 and casp-8 prevented 5-LO cleavage. Activation of casp-6 and casp-8 was connected to subsequent enhancement of cell proliferation, whereas selective caspase inhibition blocked cell growth. Last, isolated human 5-LO was cleaved by recombinant casp-6 in vitro to a 58-kDa fragment. Based on site-directed mutagenesis studies, 5-LO is cleaved by casp-6 after Asp-170, which in a homology-based 3D model of 5-LO is located on the enzyme periphery. We suggest that splitting of BL41-E95-A cells induces de novo synthesis of a protein involved in the activation of casp-6, which cleaves 5-LO.